Enhanced ionic conduction properties of alginate-PVA biopolymer blend electrolytes doped with NH4I - M. A. H., Nizam; Norfatihah, Mazuki; Nuraziliana, Muhd Ghazali; Ahmad Salihin, Samsudin (Institute for Ionics, 2025)
This study investigates the enhancement of proton conductivity in biopolymer blend electrolytes (BBEs) made from alginate and polyvinyl alcohol (PVA) doped with varying amounts of ammonium iodide (NH4I) using the solution casting technique. The infuence of NH4I on the physicochemical and ionic transport properties of the BBEs was systematically studied. Fourier transform infrared (FTIR) spectroscopy confrmed the complexation between NH4I and the polymer blend. Diferential scanning calorimetry (DSC) demonstrated that NH4I incorporation reduced the glass transition temperature (Tg) and enhanced thermal stability. Electrical impedance spectroscopy (EIS) revealed the highest ionic conductivity of 1.01×10⁻5 S cm⁻1 at 25 wt.% NH4I. The temperature dependence study showed Arrhenius behavior, with the highest conducting sample exhibiting a low activation energy (Ea) of 0.18 eV. Dielectric analysis indicated that the difusion coefcient (D), ionic mobility (μ), and charge carrier density (n) signifcantly infuenced the ionic conductivity. Using Bruce and Vincent’s technique, transference number measurements indicated that anions primarily facilitated charge transport. These fndings suggest that NH4I-doped alginate-PVA BBEs have proven potential as efective materials for electrolyte applications.